Enhancing Eco-Theology for Climate Change Education and Sustainable Development in Nigeria - Anabaraonye, Benjamin; Onnoghen, Usang N; Orji, Ijeoma E; Ewa, Beatrice O; Olisah, Nzemeka C (Sekolah Tinggi Teologi Transformasi Indonesia, 2024)
Abstract: Climate change is a global challenge that must be tackled with alacrity to achieve the sustainable development goals in Nigeria. This study highlights the need to enhance eco-theology for climate change education and sustainable development in Nigeria. This study vividly defines the concept of eco-theology. It poses the research question: “How can eco-theology enhance climate change education for sustainable development in Nigeria? The study focuses on two main objectives: First, to determine the contribution of eco-theology to sustainable development in Nigeria. Second, to identify the challenges eco-theology faces in promoting sustainable development in Nigeria. A qualitative research approach was employed, which involved analyzing data from secondary sources, including scholarly journals, books, and government records. The collected data was qualitatively analyzed based on emerging themes and patterns. The study reveals that eco-theology can be crucial in achieving sustainable development in Nigeria. Consequently, the insights from this study are valuable for eco-theologians, researchers, government officials, and scholars. It concludes with a clarion call to all passionate about solving the problems initiated by climate change to dig deeper into research towards enhancing eco-theology for climate change education and sustainable development in Nigeria.